Rare earth element modification method for chromium-nickel corrosion-resistant cladding coating
Through the rare earth element modification method of chromium-nickel corrosion-resistant clad coating, the existing coating technology is not suitable for high-temperature, long-term and low-stress service environments of large-dimensional ratio ducts, and a chromium-nickel coating with significant corrosion resistance in 750°C coal ash/flue gas environment is prepared.
Patent Information
- Application Number
- CN202411887668.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
The existing high-temperature coating technology is not suitable for high-temperature, long-term and low-stress service environments of large-level and diameter duct parts, resulting in a lack of internal wall coating preparation technology and supporting devices that meet the ultra-supercritical environment of the inner wall of the flow part and the large-level and diameter duct dimension characteristics.
The rare earth element modification method of chromium-nickel corrosion-resistant clad coating is adopted. Solid-phase clad powder is prepared by weighing and stirring according to mass ratio, and coating is prepared under an inert atmosphere in combination with plasma clad technology, and clad residue is treated.
The prepared chromium-nickel corrosion-resistant coating has a corrosion rate of less than 0.1 mg/cm2 in a coal ash/flue gas corrosion environment of 750°C. The corrosion resistance is 20 to 74 times higher than that of the base material. The coating has a high bonding strength with the base material, high production efficiency, and strong process repeatability.
Smart Images

Figure CN119753667A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material surface alloying and coating preparation, and specifically relates to a rare earth element modification method for a chromium-nickel corrosion-resistant cladding coating. Background Art
[0002] The corrosion of large aspect ratio flow components used in high temperature fields such as electricity, energy storage, and petrochemicals has become a common industry problem and technical pain point that restricts the safe production and operation of the entire energy equipment. Taking the power industry as an example, pipe blockage and pipe burst accidents caused by scale problems on the inner wall of flow components account for more than 50% of boiler non-stop accidents, resulting in an increase of more than 20% in the operating cost and material cost of the unit; therefore, research and development of anti-oxidation and corrosion-resistant technologies suitable for the inner and outer wall surfaces of pipes used in boiler units has important practical significance.
[0003] Studies have shown that high-temperature coatings are effective in solving the problems of component oxidation corrosion, wear, and high-temperature ablation. However, existing high-temperature coating technologies are mostly used for hot-end components such as aircraft engine blades, rotors, and turbine disks that have high temperatures, short action times, and small sizes. For the large aspect ratio structural characteristics of energy equipment flow components and the characteristics of high temperature, long time, and low stress service environment, existing coating technologies are no longer applicable. The entire industry is facing the dilemma of a lack of corrosion-resistant coating technology for the inner walls of flow components that meet the requirements of ultra-supercritical environments and a lack of preparation processes and supporting equipment for the inner wall coatings of components with large aspect ratio size characteristics. Therefore, it is necessary to develop a new type of oxidation-resistant and corrosion-resistant coating preparation technology and process suitable for various complex-shaped workpieces with large aspect ratios. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a rare earth element modification method for a chromium-nickel corrosion-resistant cladding coating.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a rare earth element modification method for chromium-nickel corrosion-resistant cladding coating, wherein: each solid-phase cladding powder component is weighed and prepared according to the mass ratio, and solid-phase cladding infiltrant in different proportions is prepared after stirring, ball milling and drying for standby use;
[0008] Clean the surface of the workpiece to be plated and pour enough cladding powder into the feeding port;
[0009] The workpiece is placed in an inert atmosphere for plasma cladding, and a chromium-nickel corrosion-resistant coating is obtained after cooling, and the cladding residue is treated.
[0010] As a preferred embodiment of the modification method of the present invention, the solid-phase cladding powder components include: the infiltration sources are Cr and Ni powders, the modifiers are CeO2 and Y2O3, and the activator is NH4Cl; wherein the Cr and Ni powders are sieved through a 1000-mesh sieve.
[0011] As a preferred embodiment of the modification method of the present invention, the solid phase cladding powder components are weighed by mass percentage and include 50-80% Cr, 10-40% Ni, 0-5% CeO2, 0-5% Y2O3 and 1-5% NH4Cl.
[0012] As a preferred embodiment of the modification method described in the present invention, the solid-phase cladding powder is obtained by wet-grinding the solid-phase components in a planetary ball mill and then drying them, the wet-grinding medium is anhydrous ethanol, the ball milling speed is 350-400 rpm, the time is 12-24 hours, and the drying conditions are vacuum drying at 80-120°C for 12-24 hours.
[0013] As a preferred scheme of the modification method described in the present invention, the plasma cladding process parameters include: cladding current of 80-120A, feed rate of 18-22g / min, scanning rate of 20-40cm / min, nozzle height of 8-12mm, rotation speed of 2-5r / min, ion gas flow rate of 0.2-0.3L / min, shielding gas flow rate of 18-20L / min, and inert gas of Ar or N2.
[0014] As a preferred embodiment of the modification method of the present invention, the cladding residue treatment is to wash the residue on the surface of the workpiece with a high-pressure water gun and dry it naturally.
[0015] Another object of the present invention is to overcome the deficiencies in the prior art and produce a chromium-nickel corrosion-resistant cladding coating.
[0016] As a preferred embodiment of the aluminide cladding coating of the present invention, the chromium-nickel corrosion-resistant cladding coating is uniform and dense, has good metallurgical bonding with the substrate, and has a thickness of 0.28 to 1.35 mm; the corrosion rate in a 750°C coal ash / flue gas corrosion environment is less than 0.1 mg / cm2, and the corrosion resistance is 20 to 74 times higher than that of the parent material.
[0017] Beneficial effects of the present invention:
[0018] 1. The present invention prepares the coating by plasma cladding process, which has concentrated heat, short action time, small thermal impact in the cladding area, and high bonding strength between the coating and the base material;
[0019] 2. The present invention adds rare earth oxides CeO2 and Y2O3 to the cladding powder components, which promotes the diffusion of the coating and improves the bonding strength of the membrane base;
[0020] 3. The present invention prepares the coating through an integrated production line, the coating production efficiency is high, the thickness is controllable, the process repeatability is high, and it has strong practicality;
[0021] 4. The addition of rare earth oxides in the present invention can pin grain boundaries, strengthen matrix structure, improve surface hardness, and enhance the bonding strength between coating and base material in the form of second phase precipitation on the basis of halide-promoted diffusion; in addition, rare earth oxides can reduce the critical concentration of Cr to form Cr2O3 oxide film. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0023] Figure 1 This is the tensile test specimen of the tile-shaped coating in Example 1 of the present invention (unit: mm).
[0024] Figure 2 This is the cross-sectional morphology of the coating in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0028] The raw materials used in the present invention come from:
[0029] 99.95% Cr powder was purchased from Sinopharm Chemical Reagent Co., Ltd., with the specification of Alfa-013796; 99.8% Ni powder was purchased from Sinopharm Chemical Reagent Co., Ltd., with the specification of Alfa-000663; NH4Cl was purchased from Sinopharm Chemical Reagent Co., Ltd.; 99.5% CeO2 powder was purchased from Sinopharm Chemical Reagent Co., Ltd., with the specification of Alfa-044960; 99.995% Y2O3 powder was purchased from Sinopharm Chemical Reagent Co., Ltd., with the specification of Alfa-044048; anhydrous ethanol was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0030] Instruments used in the embodiments of the present invention:
[0031] The vertical planetary ball mill was purchased from Changsha Miqi Instrument Equipment Co., Ltd., model number YXQM-2L, and the plasma cladding equipment was purchased from Shanghai Duomu Industrial Co., Ltd., model number DFB-LC402-B03;
[0032] The performance detection methods in the embodiments of the present invention are:
[0033] Smoke corrosion test:
[0034] Grind the prepared fly ash fully and add appropriate amount of acetone to make a suspension, and evenly apply it on the surface of the coating sample. The coating amount is about 50mg / cm 2 The sample was placed in a constant temperature tubular heating furnace and heated to 750°C. Mixed flue gas was continuously introduced into the tubular furnace at a flue gas flow rate of 100 mL / min. A honeycomb Pt mesh was used as a catalyst to convert SO2 into SO3. A saturated NaOH solution was used to neutralize the remaining SO2 in the tail gas at the outlet of the tubular furnace. After the corrosion test, the sample was taken out, the coal ash remaining on the surface of the sample was removed, and the sample was weighed after cleaning and drying.
[0035] Microhardness test: The hardness of the coating was measured using a HV-1000A microhardness tester. The test load was selected as 200g, the holding time was 10s, and 6 points at different horizontal positions were selected for testing. The average value was taken as the microhardness value of the coating. Bonding strength test: The coating surface of the sample was bonded to the mating part with an epoxy resin adhesive. During the bonding process, the axis of the coating sample and the mating part were kept coincident. The bonded sample was placed in a 120°C drying oven for curing for 2 hours. The test was performed on an Instron 3382 electronic bonding strength tester at a tensile speed of 0.1mm / min. The maximum tensile stress when the bonded sample broke was taken as the bonding strength between the prepared chromized coating and the substrate.
[0036] Example 1
[0037] Step 1: Weigh the solid phase components according to mass proportion, including 50% Cr, 40% Ni, 4% CeO2, 4% Y2O3 and 1% NH4Cl, place them in a planetary ball mill for wet grinding with ethanol at 400 rpm for 24 hours, and then vacuum dry them at 100°C for 24 hours to obtain cladding powder.
[0038] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and then rinse it with alcohol or acetone.
[0039] Step 3. The plasma cladding process parameters are: cladding current is 80A, feed rate is 18g / min, scanning rate is 35cm / min, nozzle height is 12mm, rotation speed is 2r / min, ion gas flow rate is 0.2L / min, shielding gas flow rate is 19L / min, and inert gas is Ar or N2; after cladding, rinse the surface residue of the workpiece with a high-pressure water gun or high-pressure air flow, and dry it naturally.
[0040] Mechanical properties test of coating samples: According to GB / T4338-2006 "High-temperature tensile test method for metal materials", the high-temperature tensile properties of coating samples are tested. The sampling position and size of the tensile sample are as follows: Figure 1 The tensile test was carried out on a CMT5205 universal testing machine at a test temperature of 630°C and a strain rate of 2×10 –4 s –1 .
[0041] The process of Examples 2 to 11 is the same as that of Example 1. Examples 1 to 11 maintain the same ratio of the penetrant components. The specific conditions are shown in Table 1. Table 1 is the specific parameters of Examples 1 to 11 of the method for preparing the chromium-nickel cladding coating on the surface of austenitic steel. According to the preparation steps in the above Example 1 and the specific preparation parameters in the table, chromium-nickel corrosion-resistant coatings of different thicknesses can be obtained. The cross-sectional morphology of the coating is as follows: Figure 2 shown.
[0042] Table 1
[0043]
[0044] By analyzing and studying the above examples, the thickness of the infiltration layer is measured to be about 0.28 to 1.35 mm. The specific results are shown in Table 1. The cross-sectional morphology of the typical coating is as follows: Figure 1 As shown in Table 1 and the cross-sectional morphology, it is found that the diffusion layer has a uniform structure, moderate thickness, sufficient diffusion of Cr atoms, a good metallurgical bond between the diffusion layer and the matrix, and is not easy to fall off.
[0045] The corrosion resistance of the chromium-nickel cladding coatings prepared in Examples 1 to 11 in coal ash / smoke at 750°C was tested. The mass changes (mg / cm2 ) as shown in Table 2
[0046] Table 2
[0047]
[0048]
[0049] It can be seen that the chromium-nickel cladding coatings prepared in Examples 1 and 4, in a 750°C coal ash / smoke environment, have poor stability of the oxide film after the corrosion time exceeds 300 h, begin to lose weight, and the oxide film peels off in large quantities; the chromium-nickel cladding coatings prepared in Examples 2 and 6 have gradually accelerated corrosion rates after the corrosion time exceeds 200 h, and their corrosion rates are 0.0111 mg / (cm 2 ·h) and 0.0114mg / (cm 2 ·h), the corrosion resistance of the coating is poor; the weight gain trend of the chromium-nickel cladding coating prepared in Examples 5, 7 and 9 within 500h conforms to the linear law, and the corrosion rate of the coating in a 750℃ coal ash / flue gas environment is basically stable; the weight gain trend of the coating prepared in Examples 3, 8, 10 and 11 conforms to the parabolic law, and the coating has good corrosion resistance in a 750℃ coal ash / flue gas environment. As the heat input of the plasma cladding process gradually increases, the thickness of the prepared chromium-nickel infiltration layer gradually increases. In addition, the increase in heat input makes the content of Cr and Ni elements in the prepared cladding coating higher, and the corrosion rate in 750℃ coal ash / flue gas is reduced. Therefore, increasing the heat input of the plasma cladding process is beneficial to improving the high-temperature corrosion resistance of the prepared chromium-nickel corrosion-resistant cladding coating.
[0050] Example 12
[0051] Step 1: Weigh the solid phase components according to the mass ratio, including 50% Cr, 40% Ni, 5% CeO2 and 5% NH4Cl, place them in a planetary ball mill for wet grinding with ethanol at 350 rpm for 24 hours, and then vacuum dry them at 100°C for 24 hours to obtain the cladding powder.
[0052] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and then rinse it with alcohol or acetone.
[0053] Step 3. The plasma cladding process parameters are: cladding current is 80A, feed rate is 20g / min, scanning rate is 40cm / min, nozzle height is 12mm, rotation speed is 3r / min, ion gas flow rate is 0.2L / min, shielding gas flow rate is 19L / min, and inert gas is Ar or N2; after cladding, rinse the surface residue of the workpiece with a high-pressure water gun or high-pressure air flow, and dry it naturally.
[0054] Example 13
[0055] Step 1: Weigh the solid phase components according to mass ratio, including 80% Cr, 10% Ni, 5% Y2O3 and 5% NH4Cl, place them in a planetary ball mill for wet grinding with ethanol at 400 rpm for 24 hours, and then vacuum dry them at 100°C for 24 hours to obtain cladding powder.
[0056] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and then rinse it with alcohol or acetone.
[0057] Step 3. The plasma cladding process parameters are: cladding current is 100A, feed rate is 18g / min, scanning rate is 35cm / min, nozzle height is 10mm, rotation speed is 3r / min, ion gas flow rate is 0.2L / min, shielding gas flow rate is 19L / min, and inert gas is Ar; after cladding, rinse the surface residue of the workpiece with a high-pressure water gun and dry it naturally.
[0058] Embodiment 14
[0059] Step 1: Weigh the solid phase components according to mass ratio, including 75% Cr, 15% Ni, 3% CeO2, 4% Y2O3 and 3% NH4Cl, place them in a planetary ball mill for ethanol wet grinding at 400 rpm for 24 hours, and then vacuum dry them at 100°C for 24 hours to obtain cladding powder.
[0060] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and then rinse it with alcohol or acetone.
[0061] Step 3. The plasma cladding process parameters are: cladding current is 120A, feed rate is 20g / min, scanning rate is 35cm / min, nozzle height is 10mm, rotation speed is 2r / min, ion gas flow rate is 0.2L / min, shielding gas flow rate is 19L / min, and inert gas is Ar; after cladding, rinse the surface residue of the workpiece with a high-pressure water gun and dry it naturally.
[0062] Embodiment 15
[0063] Step 1: Weigh the solid phase components according to mass proportion, including 60% Cr, 30% Ni, 4% CeO2, 4% Y2O3 and 2% NH4Cl, place them in a planetary ball mill for wet grinding with ethanol at 400 rpm for 24 hours, and then vacuum dry them at 100°C for 24 hours to obtain cladding powder.
[0064] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and then rinse it with alcohol or acetone.
[0065] Step 3. The plasma cladding process parameters are: cladding current is 120A, feed rate is 20g / min, scanning rate is 35cm / min, nozzle height is 10mm, rotation speed is 2r / min, ion gas flow rate is 0.2L / min, shielding gas flow rate is 19L / min, and inert gas is Ar; after cladding, rinse the surface residue of the workpiece with a high-pressure water gun and dry it naturally.
[0066] Example 16
[0067] Step 1: Weigh the solid phase components according to mass ratio, including 54% Cr, 34% Ni, 4% CeO2, 4% Y2O3 and 4% NH4Cl, place them in a planetary ball mill for wet grinding with ethanol at 400 rpm for 24 hours, and then vacuum dry them at 100°C for 24 hours to obtain cladding powder.
[0068] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and then rinse it with alcohol or acetone.
[0069] Step 3. The plasma cladding process parameters are: cladding current is 120A, feed rate is 20g / min, scanning rate is 35cm / min, nozzle height is 10mm, rotation speed is 2r / min, ion gas flow rate is 0.2L / min, shielding gas flow rate is 19L / min, and inert gas is Ar; after cladding, rinse the surface residue of the workpiece with a high-pressure water gun and dry it naturally.
[0070] The corrosion resistance of the chromium-nickel cladding coatings prepared in Examples 1 and 12 to 16 in coal ash / smoke at 750°C was tested. The mass changes (mg / cm 2 ) as shown in Table 3.
[0071] Table 3
[0072]
[0073] The corrosion rates of the chromized coatings prepared in Examples 12 and 13 gradually increased after the corrosion time exceeded 200 h, and the corrosion rates were 0.0119 mg / (cm 2 ·h) and 0.0139mg / (cm 2·h), the corrosion resistance of the coating is poor; the weight gain trend of the chromium-nickel corrosion-resistant coating prepared in Example 16 within 500h conforms to the linear law, and the corrosion rate of the coating in a 750℃ coal ash / flue gas environment is basically stable; the weight gain trend of the coatings prepared in Examples 14 and 15 conforms to the parabolic law, and the coatings have good corrosion resistance in a 650℃ coal ash / flue gas environment, among which the coating prepared in Example 14 has the lowest corrosion rate within 500h, with an average corrosion rate of 0.0088mg / (cm 2 h), reaching the complete antioxidant level.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 14 is that the solid phase components are replaced by: 75% Cr, 15% Ni, 7% CeO2 and 3% NH4Cl.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 14 is that the solid phase components are replaced by: 75% Cr, 15% Ni, 7% Y2O3 and 3% NH4Cl.
[0078] Comparative Example 3
[0079] The difference between this comparative example and Example 14 is that the solid phase components are replaced by: 75% Cr, 15% Ni, 7% La2O3 and 3% NH4Cl.
[0080] Comparative Example 4
[0081] The difference between this comparative example and Example 14 is that the proportion of the solid phase components is replaced by: 75% Cr, 18% Ni, 3% CeO2, and 4% Y2O3.
[0082] Comparative Example 5
[0083] The difference between this comparative example and Example 14 is that the solid phase composition ratio is replaced by: 75% Cr, 15% Ni, 3% CeO2, 4% Y2O3 and 3% NH4Br
[0084] The corrosion resistance of the chromium-nickel cladding coatings prepared in Example 1, Examples 12 to 16 and Comparative Examples 1 to 5 in 750°C coal ash / smoke was tested. The mass changes (mg / cm 2 ) as shown in Table 4.
[0085] Table 4
[0086]
[0087]
[0088] It can be seen that the corrosion rate of the chromium-nickel cladding coatings prepared in Comparative Examples 1 and 2 gradually accelerated after the corrosion time exceeded 200 h, and the corrosion rates reached 0.0101 mg / (cm 2 ·h) and 0.0129mg / (cm 2 ·h), the corrosion resistance of the coating is poor. In the 750℃ coal ash / flue gas environment, the coating prepared in comparative example 3 has poor stability of the oxide film after the corrosion time exceeds 300h, begins to lose weight, and the oxide film peels off in large quantities. The above comparative examples show that compared with adding only CeO2, Y2O3 or La2O3 to the deposition powder, the synergistic effect of CeO2 and Y2O3 can reduce the corrosion rate of the prepared chromium-nickel coating in 750℃ coal ash / flue gas by more than 30%, thereby further improving the corrosion resistance of the coating at high temperatures. The coating prepared in comparative example 4 also begins to peel off a large amount of oxide film after the oxidation time exceeds 300h. The corrosion rate of the chromium-nickel cladding coating prepared in comparative example 5 gradually accelerates after the corrosion time exceeds 200h, and its corrosion rate reaches 0.0128mg / (cm 2 h), the corrosion resistance of the coating is poor. The above comparative example shows that adding halide NH4Cl to the cladding powder can effectively improve the corrosion resistance of the prepared chromium-nickel cladding coating.
[0089] The bonding strength of the chromium-nickel cladding coatings prepared in Example 14 and Comparative Example 6 were tested respectively. The interface tensile bonding strength of the coating prepared in Example 14 was 42.7 MPa, while the interface tensile bonding strength of the coating prepared in Comparative Example 6 was 28.2 MPa, indicating that the plasma cladding process used in the present invention can improve the bonding strength between the coating and the substrate.
[0090] The microhardness and bonding strength of the chromium-nickel cladding coatings prepared in Example 14 and Comparative Examples 1, 2, and 3 were tested respectively. The microhardness and interface tensile bonding strength of the coating prepared in Example 14 were 403 HV and 100 HV, respectively. 0.2 and 42.7MPa, the microhardness and interface tensile strength of the coatings prepared in Comparative Examples 1, 2, and 3 are 328HV 0.2 and 27.5MPa, 281HV 0.2 and 26.4MPa, 269HV 0.2 and 23.7MPa, indicating that the rare earth oxide added to the solid phase component in the present invention can strengthen the matrix structure, improve the surface hardness, and enhance the bonding strength between the coating and the base material.
[0091] In summary, the rare earth element modified chromium-nickel corrosion-resistant cladding coating of the present invention can prepare a chromium-nickel coating with a thickness of 0.28 to 1.35 mm and good metallurgical bonding under the conditions of adjusting the main process parameters such as the cladding powder composition and plasma cladding parameters; the chromium-nickel coating obtained by the present invention has a corrosion resistance of 17 to 58 times higher than that of the parent material in a 650°C flue gas corrosion environment, and a corrosion resistance of 20 to 74 times higher than that of the parent material in a 750°C flue gas corrosion environment, which can be explained that the chromium-nickel coating prepared by the method of the present invention effectively improves the corrosion resistance of the alloy parent material in a flue gas corrosion environment. The modification method for improving the oxidation resistance of the aluminide cladding coating in the present invention is suitable for austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and various complex-shaped workpieces, and has strong practicality, high diffusion rate, excellent membrane-base bonding, and excellent industrial mass production benefits.
[0092] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A rare earth element modification method for chromium-nickel corrosion-resistant cladding coating, characterized in that: Weigh and prepare each solid phase cladding powder component according to the mass ratio, and prepare solid phase cladding infiltrant in different proportions after stirring, ball milling and drying for use; Clean the surface of the workpiece to be plated and pour enough cladding powder into the feeding port; The workpiece is placed in an inert atmosphere for plasma cladding, and a chromium-nickel corrosion-resistant coating is obtained after cooling, and the cladding residue is treated.
2. The modification method according to claim 1, characterized in that: The solid phase cladding powder components include: the infiltration source is Cr and Ni powder, the modifier is CeO2 and Y2O3, and the activator is NH4Cl; wherein the Cr and Ni powders are sieved through a 1000 mesh screen.
3. The modification method according to claim 1, characterized in that: The solid phase cladding powder components are weighed by mass percentage and include 50-80% Cr, 10-40% Ni, 0-5% CeO2, 0-5% Y2O3 and 1-5% NH4Cl.
4. The modification method according to claim 1, characterized in that: The solid phase cladding powder is obtained by wet grinding the solid phase components with a planetary ball mill and then drying them. The wet grinding medium is anhydrous ethanol, the ball milling speed is 350-400 rpm, the time is 12-24 hours, and the drying conditions are vacuum drying at 80-120° C. for 12-24 hours.
5. The modification method according to claim 1, characterized in that: The plasma cladding process parameters include: cladding current of 80-120A, feed rate of 18-22g / min, scanning rate of 20-40cm / min, nozzle height of 8-12mm, rotation speed of 2-5r / min, ion gas flow rate of 0.2-0.3L / min, shielding gas flow rate of 18-20L / min, and inert gas of Ar or N2.
6. The modification method according to claim 1, characterized in that: The cladding residue treatment is to wash the residue on the surface of the workpiece with a high-pressure water gun and let it dry naturally.
7. The chromium-nickel corrosion-resistant cladding coating obtained by the modification method as described in any one of claims 1 to 6.
8. The aluminide cladding coating according to claim 7, characterized in that: The chromium-nickel corrosion-resistant cladding coating is uniform and dense, has good metallurgical bonding with the substrate, and has a thickness of 0.28 to 1.35 mm. The corrosion rate in a 750°C coal ash / smoke corrosion environment is less than 0.1 mg / cm 2 The corrosion resistance is 20 to 74 times higher than that of the parent material.